PENGARUH PEMBERIAN PAKAN AZOLLA MICROPHYLLA TERHADAP PERTUMBUHAN IKAN NILA (OREOCHROMIS NILOTICUS) SEBAGAI RANCANGAN PEMBELAJARAN BIOLOGI SMA - Suwondo Suwondo; Darmadi Darmadi; Muhammad Amin (Biogenesis, 2021)
This study aims to determine the growth of tilapia (Oreochromis niloticus) with the use of Azolla microphylla feed and its potential to produce a module design on the material for growth and development of living things in class XII odd semester KD 3.10 and KD 4.10.This research was conducted from May to August 2020 at Danau Selais LPPM Riau University. This study used 2 stages, namely. Phase I research used quantitative descriptive to determine the growth of tilapia on Azolla microphyla feed with different feeding percentages. Fish were grouped into 3 treatments and 1 control. Fish are reared in different cages with different percentage of feeding. The research parameters included absolute length growth, absolute weight growth, nisbi  growth rate, and survival rate.Phase II research is a module teaching material design that uses 2 stages, namely, the Analyze and Design stages.The results of the experimental stage of research, feeding Azolla microphylla affected the growth of tilapia (Oreochromis niloticus). P3 treatment (giving 5% Azolla microphylla from fish biomass) is the best dose in increasing the growth of tilapia. Resulted in the absolute length growth of 4.24 cm, absolute weight 11.72 g, 4.68% relative growth, 4,68% specific growth rate and 99.4% survival rate. The P3 treatment resulted in a growth which was much lower than the P0 treatment (control).